(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This thesis in Japan education​​ system history , current situation and in Uzbekistan In Japan education​​ system management theoretical - methodological Comprehensive views are given on modern trends and approaches to the development of the fundamentals of the system.